Association between soluble transferrin receptor and systolic hypertension in adults: National Health and Nutrition Examination Survey (2007–2010 and 2015–2018) - Wang, Haoran; Qi, Qianjin; Song, Shuaihua; Zhang, Di; Feng, Li (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Hypertension increases the global burden of disease and mortality. Iron metabolism is considered to be an important factor in hypertension. However, as an indicator of iron metabolism, little is known about the associations of soluble transferrin receptor (sTfR) with hypertension. We studied the relationship between sTfR and hypertension. Methods: We studied 7416 adults aged 20 years old or above from the National Health and Nutrition Examination Survey (NHANES), a nationally representative, cross-sectional, population-based study. Weighted logistic regression was used to examine the association between markers of iron metabolism and hypertension. The restricted cubic spline (RCS) was used to characterize the association between sTfR and blood pressure. Results: Weighted logistic regression showed that higher sTfR level was associated with higher odds of hypertension (OR =1.05; 95% CI: 1.01–1.05; p = 0.001) after adjustment for all the potential confounding factors. Meanwhile, weighted logistic regression analyses indicated independent associations of high sTfR (p = 0.009) with systolic hypertension after adjusting for various different confounders. The result of restricted cubic splines showed a non-linear association between sTfR and systolic blood pressure among U.S. adults. Conclusions: sTfR was found to be an independent factor in systolic hypertension. And, a nonlinear relationship between sTfR and systolic blood pressure was discovered.